2023
DOI: 10.20473/mozaik.v23i1.40313
|View full text |Cite
|
Sign up to set email alerts
|

Making Meaning of Inanimate Objects as Characters in The Blue Umbrella (2013)

Nur Alifia Putri Saptiadi,
Mia Fitria Agustina,
Ririn Kurnia Trisnawati

Abstract: This study aims to reveal deeper and different meaning of an inanimate object, specifically umbrella, from naked eye's perspective in The Blue Umbrella Film. The Blue Umbrella Film, an animated short film directed by Saschka Unsled, employs inanimate objects as the characters as seen through the distinct human's facial expression painted on the black, blue, and red umbrellas To pursue the aim of this study, qualitative method was conducted together with Saussure's semiotic theory. The results showed that the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…Analysis of literary work and other literature subject texts using semiotic theory has been done in plenty of previous studies such as Saptiadi, Agustina, & Trisnawati (2023) that discussed characters of The Blue Umbrella; Afidah, Agustina, & Trisnawati (2022) who talked on dissecting color on the body of each god character in Lore Olympus; Haris, Agustina, & Trisnawati (2021) on focusing and explaining of the animal characters in Zootopia. The previous studies showed that semiotic study is beyond excellence to be studied.…”
Section: Richardmentioning
confidence: 99%
“…Analysis of literary work and other literature subject texts using semiotic theory has been done in plenty of previous studies such as Saptiadi, Agustina, & Trisnawati (2023) that discussed characters of The Blue Umbrella; Afidah, Agustina, & Trisnawati (2022) who talked on dissecting color on the body of each god character in Lore Olympus; Haris, Agustina, & Trisnawati (2021) on focusing and explaining of the animal characters in Zootopia. The previous studies showed that semiotic study is beyond excellence to be studied.…”
Section: Richardmentioning
confidence: 99%